The Reality of The Foreign Direct Investment Climate in Algeria Analytical and Econometrics Study for the Period: 1999-2019 - عقون شراف; غضبان مليكة (Finance and Business Economies Review, 2021)
In this research paper, we dealt with the legal development of foreign direct investments in Algeria with an analytical study of foreign direct investments coming to Algeria during the period: 2000-2018. In 2017, based on the Eviews10 program, we presented a standard study of foreign direct investment flows, so that the study model was formed from a dependent variable, which is foreign direct investment, and two independent variables, namely, GDP and inflation, during the period: 1999-2019, and the study concluded that there is a positive effect of the output Gross domestic on foreign direct investment As for inflation, the study proved the existence of a negative impact, and this is consistent with the economic theory.